Moisture sorption isotherm modeling and reverse spherification application in the production of chrysanthemum tea edible bubbles with mint leaf extract - Hidayatullah, Dimas; Hawa, La Choviya; Yulianingsih, Rini (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2026)
The chrysanthemum flower is an edible flower that is frequently processed into a dried form or used in food and beverages as edible bubbles.  Furthermore, mint leaf extract imparts a cooling sensation, enhancing the refreshing experience when consuming edible bubbles.  The storage technique for edible bubbles is a considerable challenge due to its effect on stability.  The study aimed to establish optimal storage conditions for edible bubbles by analyzing their sorption isotherm behavior and identifying the most suitable sorption isotherm model through comparison with five widely utilized models: GAB (Guggenheim-Anderson-de Boer), BET (Brunauer-Emmett-Teller), Langmuir, Peleg, and Caurie. The static gravimetric method regulates water activity (aw) between 0.057 and 0.836 (30-50 °C) utilizing saturated solutions of KOH, MgCl2, CaCl2, NaCl, and KCl.  The statistical study identified the BET model as the best model, exhibiting the type II (Sigmoid) isotherm curve. The limits of primary, secondary, and tertiary bound water content in edible bubbles were determined to be 0.084 db (aw 0.271), 0.147 db (aw 0.558), and 0.502 db (aw 0.871), respectively.  Furthermore, the study reports a decrease in isosteric and net isosteric, entropy, and Gibbs free energy, alongside with an increase in equilibrium moisture content.